PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS ) DIKOMBINASIKAN DENGAN METODE EKPERIMEN TERHADAP KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR KIMIA MAHASISWA DI PAPUA - Tiurlina Siregar; Christiana Niken Larasati (Pascasarjana Universitas Negeri Medan, 2014)
Abstract. Learning activities and critical thinking skills students of Biology at the University Ottow Geissler organic chemistry courses remains low. Lack of critical thinking skills is demonstrated by the low student learning outcomes of students. To enhance critical thinking skills and learn to apply the learning outcome types Cooperative Think Pair Share ( TPS ). The population was students of Biology, University of Papua years teaching Ottow Geissler 2012/2013 consists of 10 students. This study aims to determine the relationship of cooperative learning model Think Pair Share ( TPS ) through the experimental method to the results of students of the University Ottow berajar Geissler ( Sub Topic Hydrocarbon Compounds ). Relationship learning model is designed based on the results of preliminary studies, further validated by experts then tested the students of Biology, University of Ottow Geissler using purposive sampling. Is a quantitative research instrument. Quality of the instrument based on the validity and reliability of the instrument in the form of questionnaires and tests. The conclusion from this study is that there is a fairly strong relationship cooperative learning model Think Pair Share ( TPS ) Method Through Experiment Against the critical thinking skills of 0.5730 and has dealt cooperative learning model Think Pair Share ( TPS ) with the learning outcome of -0.719. Keywords: Cooperative Learning Model, Type Think Pair Share (TPS) Critical Thinking, Learning Outcomes, Hydrocarbons